Pelatihan Investasi Saham Bagi Generasi Millenial Di Pasar Kerkap Bengkulu Utara - Indah Oktari Wijayanti; Halimatusyadiah Halimatusyadiah; Nikmah Nikmah (Universitas 45 Surabaya, 2024)
This investment in real wealth must be invested in the long term to make a profit. However, investments in the capital market that are invested in the short term will provide benefits. This phenomenon is an opportunity to provide education to the public in increasing knowledge about investing in the capital market, especially stocks. Shares are certificates that show proof of ownership of a company (Tandelilin; 2010). This is very important because basic investment knowledge will be able to prevent people from entering into irrational investment practices and illegal investments. Therefore, an educational program on capital market investment, especially stocks, is needed. One of the educational programs is capital market training targeting the public as potential investors. This program is in collaboration with the Indonesian Stock Exchange Investment Gallery (GI-BEI) Faculty of Economics and Business, University of Bengkulu. The community in Pasar Kerkap Bengkulu Utara is one of the people who are interested in deepening their knowledge of investing in the capital market, especially stock products. With this capital market training, it is hoped that the community will become active investors in the capital market using technical analysis, so as to improve the welfare of the community.